Menakar Tingkat Kepuasan Mahasiswa SPs UHAMKA Terhadap Kualitas Penyelenggaraan Pendidikan - Imam Safi'i; Ishaq Nuariadin (Universitas Muhammadiyah Surakarta, 2020)
The level of student satisfaction with the educational process has a very important role in supporting the sustainability of an institution. This study aims to describe the level of satisfaction of SPs students. UHAMKA who has graduated in the academic year 2018/2019 on the organization of education that took place at the Graduate School. This research was conducted using survey methods. The instrument used to measure the level of student satisfaction is a number of structured questions related to leadership, learning, facilities and infrastructure, as well as the impact of studies at UHAMKA on career development. The results showed that the level of student satisfaction at the UHAMKA Graduate School was very satisfying. Quantitatively the average student satisfaction was 88.03. The results of this study can be used as a basis for evaluating and developing follow-up efforts for leaders in the UHAMKA graduate school environment.